Hazardous State Analysis of Landslide Mass Based on Cumulative Displacement of Landslide - WANG Chaoyang; LI Limin; WANG Lianxia; REN Ruibin; FU Zhentao; CUI Chengtao (Renmin Zhujiang)
To solve the problem of incomplete analysis of individual landslide hazardous states,this paper proposes a multiple perspective analysis method of landslide's hazardous state based on landslide cumulative displacement.Firstly,the limit displacement criterion is used to determine the early warning stage where the landslide locates.Secondly,the landslide stable state is evaluated by the cusp mutation theory.Thirdly,the development trend of the landslide mass is determined by using rescaled range analysis.Then,the fuzzy matrix is established to determine the hazardous state of the landslide.However,since a single detection point cannot accurately reflect the overall hazardous state of the landslide,multiple monitoring points are used to identify the overall hazardous state of the landslide.Finally,the method is applied to the Bazimen landslide to verify its effectiveness.The results show that this method can effectively identify the local and the whole hazardous state of the landslide.